Patterns and intrinsic fluctuations in semi-dilute motor-filament systems - Swaminathan, Sumanth; Ziebert, Falko; Aranson, Igor S.; Karpeev, D. (epl, 2010)
We perform Brownian dynamics simulations of molecular motor-induced ordering and structure formations in semi-dilute cytoskeletal filament solutions. In contrast to the previously studied dilute case where binary filament interactions prevail, the semi-dilute regime is characterized by multiple motor-mediated interactions. Moreover, the forces and torques exerted by motors on filaments are intrinsically fluctuating quantities. We incorporate the influences of thermal and motor fluctuations into our model as additive and multiplicative noises, respectively. Numerical simulations reveal that filament bundles and vortices emerge from a disordered initial state. Subsequent analysis of motor noise effects reveals: i) Pattern formation is very robust against fluctuations in motor force; ii) bundle formation is associated with a significant reduction of the motor fluctuation contributions; iii) the time scale of vortex formation and coalescence decreases with increases in motor noise amplitude.
Gesehen am 23.09.2022